Biofabrication: 'Printability' of Candidate Biomaterials for Extrusion Based 3D Printing: State‐of‐the‐Art (Adv. Healthcare Mater. 16/2017). Issue 16 (August 2017) - Kyle, Stuart; Jessop, Zita M.; Al‐Sabah, Ayesha; Whitaker, Iain S.
Abstract : 3D bioprinting has the potential to replicate complex tissue architecture and biomanufacture physiologically relevant multicellular constructs on demand. In article number1700264, Stuart Kyle, Iain S. Whitaker, and co‐workers review a new generation of bioinks with suitable biocompatibility and high shape/print fidelity, that have the potential to match or exceed the physical, chemical and biological properties of human tissue, when combined with the appropriate cell source.